48th Annual Convention of the Master Plumbers of California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 48th Annual Convention of the Master Plumbers of California, held May 2-4, 1949 in San Jose California. The group is assembled out of doors in front of the San Jose Civic Auditorium.